New Inscriptions from the Museum of Eskişehir - Nalan Eda Akyürek Şahin; Hüseyin Uzunoğlu (Gephyra, 2019)
The authors have been working on the unpublished Greek and Latin inscriptions preserved at the museum of Eskişehir for many years. In this contribution 43 new inscriptions are presented which have been recorded over previous years. Amongst these are 38 funerary inscriptions, one is possibly a dedication (no. 15) and another is an inscription on a ring (no. 40). The last 3 artefacts (nos. 41-43) are inscribed bread stamps. Two of the funerary inscriptions are epigrams (nos. 33-34). The funerary inscriptions are carved on stelai, on altars, as well as on columns. These artefacts were discovered within the province of Eskişehir, but the exact find-spot and provenance of these inscriptions are largely unknown. They are mostly dated to the period between the second-third and fourth-sixth centuries A.D., however, two of the bread stamps date from a very late period, presumably to the eleventh century A.D.